Differences in soccer kick kinematics between blind players and controls - Giagazoglou, P.; Katis, A.; Kellis, A.; Natsikas, C. (Adapted Physical Activity Quarterly, 2011)
The purpose of the current study was to examine the kinematic differences during instep soccer kicks between players who were blind and sighted controls. Eleven male soccer players who were blind and nine male sighted performed instep kicks under static and dynamic conditions. The results indicated significantly higher (p < .05) ball speed velocities (20.81m/sec) and ball/foot speed ratio values (1.35) for soccer players who were blind during the static kick compared with sighted players (16.16m/sec and 1.23, respectively). Significant group effect on shank and foot angular velocity was observed during the static kicking condition (p < .05), while no differences were found during the dynamic kicking condition (p > .05). Despite the absence of vision, systematic training could have beneficial effects on technical skills, allowing athletes who are blind to develop skill levels comparable to sighted athletes.